Peningkatan Derajat Kesehatan dengan Promosi Pola Hidup Bersih dan Sehat di Panti Asuhan Tebet, Jakarta Selatan - Putri Winda Lestari; Partogi Michael Jordan; Adham Herlambang Adi Chandra; Bima Badruzzaman; Sofi Latifah Lestari (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
Sanitary behavior is a set of behaviors that are practiced based on awareness as a learning outcome, which makes a person, family, group, or community able to help themselves (independent) in the health sector and play an active role in realizing public health. The orphanage is a business institution to improve child welfare in alleviating child neglect. Environmental conditions in the orphanage are often ignored, causing the orphanage residents to suffer illness. Knowledge about sanitary behavior has also never been obtained by foster children because not many people care about this condition. The Tebet Orphanage is an orphanage located in South Jakarta, with most of the foster children at school-age. School-age children are an age group that is vulnerable to health problems. The initial survey shows that sanitary behavior has not been implemented in an orphanage properly. Therefore, it is necessary to educate about sanitary behavior. The target of this activity is to increase knowledge and understanding of sanitary behavior so that later foster children can implement clean and healthy lifestyles in their daily lives. The method used is to increase understanding or education about sanitary behavior. From the results of this activity, it can be seen that participants can understand the material presented. They are enthusiastic and active in the discussion. A similar program is needed so that community service activities are sustainable.